A Study Efficiency and the Result of High Vocational Certificate in Agriculture Student by Using Teaching Document on Anatomy and Physiology of Domestic Animals - รัตนวัน วรวุธ (Journal of Vocational Education in Agriculture, 2019)
The purposes of this research were to study efficiency and the result of academic achievement of High Vocational Certificate in Agriculture student who being taught by using Teaching Document on Anatomy and Physiology of Domestic Animals on Reasoning with 80/80 percent standardize criterion and had academic achievement statistically higher than before the experiment. The subjects of this study were 15 High Vocational Certificate in Agriculture student of Ubonratchathani College of Agriculture and Technology, Muang District, Ubonratchathani, who being learn in Anatomy and Physiology of Domestic Animals, during the first semester of 2016 academic year. The Experimental measurement is Examination paper of Teaching Document on Anatomy and Physiology of Domestic Animals, The data were statistically analyzed by using t – test one – group. The results of this study revealed that : Academic achievement of High Vocational Certificate in Agriculture student who being taught by using Teaching Document on Anatomy and Physiology of Domestic Animals on Reasoning with 87.70/84.13, had achieved 80/80 percent standardize. The Reasoning had before academic achievement test 76.33 (S.D. = 2.0) or 50.87% and after academic achievement test 126.27 (S.D. = 2.99) or 84.18% and academic achievement statistically higher than before the experiment at the .01 level of Highly-significance.